2007
DOI: 10.1097/icu.0b013e32808373a2
|View full text |Cite
|
Sign up to set email alerts
|

Evolving global risk assessment of ocular hypertension to glaucoma

Abstract: The aim of assessing global risk for conversion from ocular hypertension to glaucoma is to identify patients who are most likely to benefit from early treatment. Calculation of risk should be accompanied by thorough analysis of risks, benefits, and alternatives for the individual patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Validated risk calculators have become a useful tool in risk assessment for coronary heart disease (CHD),13 and parallels have been drawn between CHD and glaucoma; both are chronic diseases with known modifiable risk factors 14 15. Prediction models often do not generalise beyond the population used to derive them, and so it is widely accepted that a prediction model should not be applied in clinical practice before it has been validated in at least one other population and preferably by different investigators 16.…”
Section: Introductionmentioning
confidence: 99%
“…Validated risk calculators have become a useful tool in risk assessment for coronary heart disease (CHD),13 and parallels have been drawn between CHD and glaucoma; both are chronic diseases with known modifiable risk factors 14 15. Prediction models often do not generalise beyond the population used to derive them, and so it is widely accepted that a prediction model should not be applied in clinical practice before it has been validated in at least one other population and preferably by different investigators 16.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the goal of medical and surgical treatment is not only to halt disease progression but also to effectively manage risk factors to prevent conversion to disease, much in the same way that elevated blood pressure is managed to prevent coronary artery disease. 2,3 One important risk factor for the progression of glaucomatous damage is ocular hypertension, that is, sustained elevation of intraocular pressure (IOP) above 21 mmHg. 3 Other risk factors for the disease include family history of glaucoma or asymmetric cup-to-disc ratio.…”
mentioning
confidence: 99%
“…2,3 One important risk factor for the progression of glaucomatous damage is ocular hypertension, that is, sustained elevation of intraocular pressure (IOP) above 21 mmHg. 3 Other risk factors for the disease include family history of glaucoma or asymmetric cup-to-disc ratio. 4,5 Clinicians must consider the IOP, pachymetry readings, visual fields, gonioscopy and optic nerve head assessment when making decisions on whether to treat or observe.…”
mentioning
confidence: 99%
“…The data suggested that also we must consider all risks, as well as benefits and alternatives for this serious ophthalmological problem (17,18).…”
Section: Discussionmentioning
confidence: 99%